2021
DOI: 10.1002/jobm.202100494
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic colonization of entomopathogenic fungi increases plant disease resistance by changing the endophytic bacterial community

Abstract: Various mechanisms are involved in plant disease resistance mediated by entomopathogenic fungi; however, the role of plant endophytic microbes in disease resistance is unknown. In the present study, we showed that the disease incidence of northern corn leaf blight caused by Exserohilum turcicum (Et) on maize was reduced significantly by soil inoculation with Beauveria bassiana (Bb). Meanwhile, B. bassiana colonization and E. turcicum infection increased the diversity and abundance and diversity of endophytic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…For example, Berendsen et al (2018) indicate that plants could adjust their root microbiome following pathogen infection and specifically recruit disease resistance-inducing and growth-promoting microbes, which potentially enhance the survival potential of their offspring that would grow in the same soil. Similarly, Chang et al (2021) showed that B. bassiana colonization and Exserohilum turcicum infection increased the relative abundance of plant beneficial bacteria ( Burkholderia and Pseudomonas ) in maize leaves significantly, with positive biological control and plant growth promotion effects. Our study highlights that plants can regulate EPF distribution in plant tissues and their own defense responses under abiotic stress.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Berendsen et al (2018) indicate that plants could adjust their root microbiome following pathogen infection and specifically recruit disease resistance-inducing and growth-promoting microbes, which potentially enhance the survival potential of their offspring that would grow in the same soil. Similarly, Chang et al (2021) showed that B. bassiana colonization and Exserohilum turcicum infection increased the relative abundance of plant beneficial bacteria ( Burkholderia and Pseudomonas ) in maize leaves significantly, with positive biological control and plant growth promotion effects. Our study highlights that plants can regulate EPF distribution in plant tissues and their own defense responses under abiotic stress.…”
Section: Discussionmentioning
confidence: 93%
“…Beauveria bassiana, an endophytic fungus in northern corn (Zea mays L.), inhibited the relative abundance of phytopathogenic fungi Exserohilum turcicum by increasing the plant beneficial bacteria. 23 A. oxytropis dominated the endophytic fungi in many locoweeds. With the increase of the abundance of A. oxytropis, the microbial diversity indexes (Shannon and Simpson) of Nicotiana tabacum cultivar K326 leaf were significantly changed, and five pathogenic bacteria were inhibited by A. oxytropis.…”
Section: ■ Discussionmentioning
confidence: 97%
“…Dhayanithy et al found that endophytic fungi in Catharanthus roseus could produce some secondary metabolites with biological activities such as eliminating free radicals. Beauveria bassiana, an endophytic fungus in northern corn ( Zea mays L.), inhibited the relative abundance of phytopathogenic fungi Exserohilum turcicum by increasing the plant beneficial bacteria A.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous EPF strains have a plant disease control effect via endogenous colonization ( Bamisile et al, 2018 ; Vega, 2018 ). Some strains showed no directly antagonistic effects against pathogens in vitro but can improve plant resistance to diseases following endogenous colonization by altering the phyllosphere microbiome of maize after colonization ( Chang et al, 2021 ) or regulating salicylic acid (SA) and jasmonic acid (JA) pathways ( Qin et al, 2021 ; Gupta et al, 2022 ). Nevertheless, EPF exhibited direct antagonism against pathogens via antibiosis, competition, or parasitism through the production of fungal secondary metabolites ( Ownley et al, 2008 ; Vega et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%